Pemetaan Pengetahuan Ibu Rumah Tangga Tentang Makanan Sehat dan Perilaku dalam Pemilihan Makanan Bagi Keluarga Dimasa Pandemi Covid-19 - Aditya Febrian; Guspri Devi Artanti; Mahdiyah Mahdiyah (Publikasi Indonesia, 2023)
Knowledge of housewives about healthy food and behavior in choosing food for the family is very important, especially during a pandemic where the body needs good nutrition so that it is not easily infected with the Covid-19 virus outbreak. The purpose of this study was to find out the results of Mapping Knowledge of Housewives About Healthy Food and Behavior in Food Choices for Families During the Covid-19 Pandemic (Study on Housewives in Rusun Jatinegara Kaum). This research was conducted in the Rusun Jatinegara Kaum, from October 2020 to August 2022. The population and this research are housewives who live in the Rusun Jatinegara Kaum. This research method is descriptive quantitative research using a correlational approach. The instrument used in this study was a questionnaire with a Likert scale. Based on the results of the questionnaire answers from respondents for the sub-indicator of implementing a routine daily eating schedule, there were 45% of respondents who answered always, 26% of respondents answered often, 16% answered sometimes, 4% answered rarely and 10% answered never. Then the results of the questionnaire answers from respondents for the sub-indicators of the meal menu based on meal times, 21% of respondents answered always, 25% of respondents answered often, 30% answered sometimes, 6% answered rarely and 18% answered never. Then the results of the questionnaire answers from respondents for sub-indicators of types or food menus based on nutrients, 15% of respondents answered always, 25% of respondents often answered. 33% answered sometimes, 6% said rarely and 21% said never. Then the results of the questionnaire answers from respondents for sub-indicators implementing food portions according to needs, 26% of respondents answered always, 43% of respondents answered often, 26% answered sometimes, 0% answered rarely and 6% answered never.